Religiosity and transparency in the management of zakat institutions - Fadzli, Adam; Roshaiza, Taha; Nurul Nurhidayatie, Muhamad Ali; Akmalia, M. Ariff (2017)
To date, the accessibility of zakat information, specifically concerning collection and distribution, is very limited. As the information is not publicly accessible, it suggests a low level of transparency in zakat institutions. Realizing this, our study aims to explore the concept of transparency in zakat institutions in Malaysia and how it correlates with the dimension of religiosity. Data were collected from interviews with selected key informants and the observation of annual reports of zakat institutions for 14 states in Malaysia. The results from both the interviews and the review of annual reports support the low level of transparency practised by zakat institutions. The contribution of this study is twofold. Firstly, the public, regardless of payer or recipient, should know their right to obtain first-hand information from zakat institutions. Secondly, the findings may shed light on how the zakat institutions can further improve their management systems.